Utilization of Flywheel Generators with Inertial Loads To Produce Optimal Power - Hidayat, Royan; Willis, Galuh Renggani; Farid, Ahmad (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
The increasing need for electrical energy encourages the development of more efficient alternative energy sources. This study aims to analyze the utilization of flywheel-based electric generators with inertial loads to produce optimal output power.The research method used is an experiment, by testing a flywheel-based electric generator with variations in flywheel mass, namely 26 kg, 28 kg, and 54 kg. Testing is carried out by measuring the rotational speed of the shaft, torque, and output power produced under various operational conditions.The results of the study showed that the use of a flywheel contributed to maintaining the stability of the generator rotation speed, so that the output power produced was more consistent. From the test results, a flywheel with a mass of 26 kg produced an optimal output power of 367.6 W compared to other flywheels. The flywheel is also able to store mechanical energy and release it as needed, increasing system efficiency. The conclusion of this study is that a flywheel-based generator with an inertial load can be a potential solution in the development of more efficient and sustainable alternative power plants.